Synthesis of 4,4′-bis(nonafluorobiphenyl-4-oxyphenyl)-bis(trifluoromethyl)methane and a ladder polyether with spirobisindane fragments on its base - Tkachenko I.М.; Kobzar, Ya. L.; Shekera О.V.; Shevchenko, V.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
A method of synthesis of 4,4′-bis(nonafluorobiphenyl-4-oxyphenyl)-containing monomer with 1,1,1,3,3,3-hexafluoropropane fragment based on decafluorobiphenyl and 4,4′-(hexafluoroisopropylidene)diphenol is developed. Ladder-type fluorinated aromatic polyether having both perfluorinated aromatic units and CF3-groups, as well as both rigid dibenzodioxin and spirobisindane fragments, is synthesized by the interaction of the obtained monomer with 5,5′,6,6′-tetrahydroxy-3,3,3′ ,3′-tetramethyl-1,1′-spirobisindane. The structures of the prepared monomer and the polymer were determined using 1H, 19F NMR and IR spectroscopy techniques. It is shown that the synthesized polyether has high glass transition temperature and good thermooxidative stability.